2011
DOI: 10.1007/s11805-011-0568-6
|View full text |Cite
|
Sign up to set email alerts
|

MTDH expression in invasive micropapillary carcinoma of the breast

Abstract: OBJECTIVE To clarify the expression of MTDH in invasive micropapillary carcinoma of the breast (IMPC) and analyze the relationship between MTDH expression and clinicalpathologic parameters of the IMPC patietns. METHODS The expression of MTDH protein was analyzed using immunohistochemical staining in 86 cases with IMPC and another 86 cases with invasive ductal carcinoma not otherwise specified (IDC-NOS). The association between MTDH expression and clinicalpathologic parameters of the IMPC patients was analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…33,58 Many genes related to maintaining polarity, cilia formation, and cell morphology are located in these regions. Hao et al 59 compared the expression of prostate stem cell antigen (PSCA) gene located at 8q24 in 66 cases of IMPCs and 67 cases of ICD-NOSs and found that its expression was significantly greater at both the protein and messenger RNA levels in IMPC than it was in IDC-NOS. They concluded that PSCA might have an important role in the LNM of IMPC.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%
“…33,58 Many genes related to maintaining polarity, cilia formation, and cell morphology are located in these regions. Hao et al 59 compared the expression of prostate stem cell antigen (PSCA) gene located at 8q24 in 66 cases of IMPCs and 67 cases of ICD-NOSs and found that its expression was significantly greater at both the protein and messenger RNA levels in IMPC than it was in IDC-NOS. They concluded that PSCA might have an important role in the LNM of IMPC.…”
Section: Mechanism Of Metastasismentioning
confidence: 99%
“…rs2294008 or rs2978974) are associated with increased risk of developing breast cancer [ 24 ]. Moreover, there is some evidence by two preliminary studies suggesting that PSCA-protein might be expressed in at least a subpopulation of breast cancer patients [ 25 , 26 ]. However one of these studies only focusses on a limited set of patients with micropapillary carcinoma of the breast.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent GWAS studies have shown that two single-nucleotide polymorphisms (SNPs) in PSCA gene are associated with gastric cancer [44]. Hao et al (2011) have reported the PSCA expression in invasive micropapillary carcinoma of breast [45]. CYP11B2 residing in the same region has been associated with adrenocortical tumor development [46].…”
Section: Discussionmentioning
confidence: 99%